Micropropagation of wasabi plant (Wasabia japonica Matsumura) by shoot apex culture - Hung, Cao Dinh; Minh, Nguyen Tri; Ai, Nguyen Trung; Dieu Huong, Nguyen Thi (Academia Journal of Biology, 2015)
The mass propagation technique by shoot apex culture of the wasabi plant (Wasabia japonica Matsumura) was established as follows: 1. Shoot apexes isolated from rhizomes were used as explants. In order to regenerate vigorous shoots, the explants were cultured on the half-strength MS basal medium supplemented with antibiotics. 2. For optimal multiple-shoots, the explants were cultured on the half-strength MS basal medium supplemented with a combination of BA at 0.1 mg/l and NAA at 0.02 mg/l within 30 days of culture. The addition of the activated charcoal at 0.1g/l to the root regeneration medium, which had been supplemented with 0.1mg/l of NAA, was necessary. The result also showed that, after 8 months of transplantation and acclimatization, the plants with survival rate of 90-97% began to shoot and grew well under the greenhouse conditions. Through this study, a large number of synchronous and bacteria-free plantlets were simultaneously obtained to meet the great demand of the local farmers and the japanese-owned enterprises in Dalat region for growing and processing the wasabi plant.